Pendampingan Faktor Faktor Penyebab Keterlambatan Pembangunan Jembatan Karang Semanding Kabupaten Jember - Dofir Surya Saputra; Ferdi Hidayat; Aminatus Zahriyah (Lembaga Pengembangan Kinerja Dosen, 2023)
The bridge at Karang Semanding was the reason for choosing the location due to a delay in the progress of the project construction which was scheduled to start on February 14 2023 and was targeted for completion on June 13 2023 but until March 14 2023 the implementation of the work had not started by the implementing party, namely CV. Bima Putra Nusantara. This service activity is carried out to analyze the factors causing delays in the Karang Semanding Bridge construction project. This mentoring activity aims to provide an accelerated approach in terms of pursuing delays in the construction of the Karang Semanding Bridge. Second, post-determination assistance, namely making questionnaires, processing data, analyzing the data that has been obtained from the questionnaires and then conclusions are drawn using the influence index test approach, frequency index, and interest index. The results of this assistance are carried out from identifying what factors cause delays. Factors causing delays in the construction of the Karang Semanding Bridge with the highest interest index value are technical factors with an interest index value of 48.1% and assistance providing an accelerated approach to delays in the construction of the Karang Semanding Bridge which is a reference for partner decision making, namely CV. Bima Putra Nusantara in the form of pre-orders for precast materials and the quantity and quality of workers that must be added.